2020
DOI: 10.1016/j.nmni.2020.100806
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical symptoms after Helicobacter pylori eradication in functional dyspepsia patients based on endoscopic view of antral gastropathy

Abstract: Functional dyspepsia is a common gastric disease that can be associated with Helicobacter pylori infection. The aim of this study is to evaluate antral endoscopy of individuals who presented with functional dyspepsia, H. pylori infection status and the effects of eradication therapy on the symptoms. Following the diagnosis of dyspepsia as per Rome III criteria, 260 individuals who were eligible for the study underwent upper gastrointestinal endoscopy and were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The ure C gene copy number was used to determine the number of H. pylori in biopsy samples, which were positive at a copy number of 4.78×10 9 and produced a Cq value of 11.64. When a dog with a history of chronic vomiting was tested histopathologically, it was found that it had symptoms of chronic enteritis duodenitis H. pylori infection alters acids in the duodenum, produces abnormal duodenal movement that cause chronic enteritis, and leads to manifestations of ulcerative colitis [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ure C gene copy number was used to determine the number of H. pylori in biopsy samples, which were positive at a copy number of 4.78×10 9 and produced a Cq value of 11.64. When a dog with a history of chronic vomiting was tested histopathologically, it was found that it had symptoms of chronic enteritis duodenitis H. pylori infection alters acids in the duodenum, produces abnormal duodenal movement that cause chronic enteritis, and leads to manifestations of ulcerative colitis [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The clinical diagnosis of H. pylori infection is conventionally performed by tests, such as the rapid urease test (RUT), [ 146,147 ] serological tests, [ 148,149 ] invasive endoscopy, [ 150,151 ] and stool antigen test (SAT). [ 152,153 ] However, some drawbacks of these tests have been reported, such as limitations in young children and pregnant women (related to UBT: 14 C‐urea breath test), [ 154,155 ] low sensitivity and acceptability (related to serum antibody test and invasive endoscopy), [ 156 ] appearance of false negative results in low bacterial infections (related to SAT).…”
Section: Drug Delivery Systems (Ddss) In the Fight Against H Pylorimentioning
confidence: 99%
“…Dyspepsia accounts for 40% of visits to gastrointestinal clinics, making it one of the most common causes for referrals. 1 Quite possibly of the most common functional gastrointestinal problem (FGIDs), functional dyspepsia (FD), is described by upper stomach distress and/ or distress without organic abnormalities. The epigastric pain syndrome and postprandial distress syndrome subsets of FD were separated by the Rome IV Consensus.…”
Section: Introductionmentioning
confidence: 99%